PHONOLOGY AND MORPHOLOGY INTERFERENCES IN BUKALAPAK ADVERTISEMENT JANUARI-JULY 2017 EDITION - Ratnawati Ratnawati; Tri Pujiati (Institut Agama Islam Negeri Palopo, 2019)
This research is aimed at explaining the form of language interferences in bukalapak advertisement edisi during January - July 2017. This research used descriptive qualitative method through sociolinguistics approach. The object of the research were the utterances in the Bukalapak advertisement which display by official youtube during Januari up to July 2017. The total number of data used was 131 data. Those data were collected through recording and notetaking. Based on the data analysis, it is found that there is interferences in the Bukalapak advertisement which display by official youtube during Januari up to July 2017. The phonology interferences is divided into two types namely deletion of the sound and addition of the sound. While the morphology interference is the errors in affixation on some Indonesian words.